'+ design – waste': a project for upcycling refuse using design tools. (1st January 2013) - Santulli, Carlo; Langella, Carla
This work introduces and describes a number of projects, which are aimed at reusing waste materials in design objects, aiming at reducing the environmental impact of their disposal, by providing to them an added value. This would also allow verifying specific opportunities for development offered by this approach to innovation and revaluation of productive sectors, in particular focusing on small and medium enterprises (SMEs) operating locally. A methodology was followed, which was based upon the integration of different know-how and oriented to promote the glitch of creativity process. Waste used included polystyrene disposable crockery, woodchips, molten rock powder and kaolin, steel plates and glass. This approach may offer results in different contexts, at different scales and in different market sectors, conferring added value to disposed materials, by 'upcycling' them. In this respect, it is also proposed that other applications, involving either the same materials or other wastes that are difficult to be collected and recycled are developed in the future.